Structural and Electrical Conductivity Properties of a Newly Synthesized 3-Methoxybenzylammonium Cation Diphosphate - A. Elboulali; S. Akriche; M. Rzaigui; S. S. Al-Deyab (E-Journal of Chemistry)
The structure of the newly synthesized material, [3-(CH3O)C6H4CH2NH3]2H2P2O7 can be described as inorganic layers (H2P2O72-)n stacked perpendicular to the c-axis at z = 0 and z = 1/2 interleaved with organic cations [3-(CH3O)C6H4CH2NH3]+. The connection of the independent entities are assured by a set of N—H…O and C—H…O H-bonds in addition to electrostatic and Van der Waals interactions, generating a non-centrosymetric three-dimensional network. On the basis of electrical conductivity measurements, it was found that, at higher temperature conductivity increases linearly, showing medium conducting behaviour of the organic diphosphate salt with values lying in the range of σ= 0.69 10−4 Ω−1cm−1 at 328 K to 2.66 10−4 Ω−1cm−1 at 405 K and activation energy of Ea = 0.23 eV. Its characterization by IR absorption spectroscopy is described too.